Studies of ion transport and electrochemical properties of plasticized composite polymer electrolytes - D. Hambali,; Z. Zainuddin,; I. Supa’at,; Z. Osman, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The composite polymer electrolytes (CPEs) composed of polyacrylonitrile (PAN) as host polymer, lithium tetraflouroborate (LiBF4) as dopant salt, dissoÅlved in the mixture of ethylene carbonate (EC) and dimethyl phthalate (DMP) as plasticizing solvent, with the addition of silica (SiO2) as inorganic filler were prepared by the solution casting technique. The CPE films were prepared by varying the concentrations of SiO2 from 1 to 5 wt. %. The CPE film containing 3 wt. % of SiO2 exhibits the highest ionic conductivity of 1.36 × 10-2 S cm-1 at room temperature while for temperature dependence studies, the plot obtained obeyed Arrhenius rule and the calculated activation energy was 0.11 eV. The ionic conductivity of the CPEs was found to depend on the concentration of ion pairs of dopant salt as showed by FTIR spectra. The calculated value of lithium ions transport number, tLi+ for the highest conducting CPE film was 0.15. This result indicates that anionic species are the main contributor to the total conductivity of the CPE. The CPE film has an electrochemical stability higher than the non-filler film.